Inter-Individual Variability of a High-Intensity Interval Training With Specific Techniques vs. Repeated Sprints Program in Sport-Related Fitness of Taekwondo Athletes - Ojeda-Aravena, Alex; Herrera-Valenzuela, Tomás; Valdés-Badilla, Pablo; Cancino-López, Jorge; Zapata-Bastias, José; García-García, José Manuel (Frontiers in Physiology, 2021)
This study investigated the effect of 4 weeks high-intensity interval training (HIIT) with specific techniques (TS-G) vs. 5 m repeated sprints (RS-G) program and analyze the inter-individual responses (classified in responders (Rs) and non-responders (NRs)) on sport related fitness in taekwondo athletes. Athletes of both genders (n = 12) were randomly assigned into TS-G and RS-G groups. Both groups trained 3 days/week for 4 weeks (2 blocks of 3 rounds of 2 min of activity [4 s of all-out efforts with 28 s dynamical pauses] with 1 min of passive rest in between and 5 min between blocks) during their regular training. Related sport fitness assessments included squat jump (SJ), countermovement jump (CMJ), multiple frequency speed of kick test (FSKTMULT), specifically total kicks and kick decrement index (KDI) and 20-metre shuttle run (20MSR). Relevant results indicate a significant effect of the time factor in both groups for SJ performance and a significant decrease for KDI on RS-G. In addition, an improvement in performance according to effect size analysis in the TS-G in total kicks, KDI and 20MSR. Complementarily, a higher proportion of athlete Rs was reported in TS-G vs. RS-G for SJ (50% vs. 30.3%, respectively), CMJ and total kicks (16.6% vs. 0%). In conclusion, the addition to regular training of a HIIT technique-specific and 5 m repeated-sprints protocols with intervals during 4 weeks of training can improve the shortening characteristics of lower limb performance, although they were not sufficient stimuli in the other components of taekwondo-related fitness.